Decentralized Autonomous Organizations—Governance, Technology, and Legal Perspectives (Springer Nature, 2025)
This open access book explores the transformative world of DAOs, where decentralized governance meets blockchain technology. Based on a competitive peer-reviewed selection of papers presented at the second European DAO Workshop at ZHAW Zurich University of Applied Sciences in Zurich, Switzerland in 2025, this book provides an in-depth analysis of the current state of DAO research. In this context, it addresses key aspects of DAOs, from governance mechanisms and stakeholder dynamics to the development of essential tools and frameworks. Beyond examining how DAOs can redefine organizational structures, enhance transparency, and promote democratic decision-making, it also addresses important challenges such as centralization risks, legal uncertainties, and integration into existing economic and regulatory frameworks. This book is valuable for researchers and practitioners interested in understanding and promoting the potential of DAOs in creating a fairer and more innovative digital economy.